A spectrally bright wavelength-switchable vacuum ultraviolet source driven by quantum coherence in strong-field-ionized molecules. (8th February 2021) - Wan, Yuexin; Liu, Zhaoxiang; Yao, Jinping; Xu, Bo; Chen, Jinming; Zhang, Fangbo; Zhang, Zhihao; Qiao, Lingling; Cheng, Ya
Abstract: We report generation of spectrally bright vacuum ultraviolet (VUV) and deep UV (DUV) coherent radiations at the wavelengths of 192 nm, 198 nm and 204 nm. These DUV/VUV radiations originate from resonant four-wave mixing assisted by quantum coherence in tunnel-ionized CO molecules. The electronic coherence is created when the pump pulses resonantly excite electronic transitions of CO + . The technique allows for the selective switch of DUV/VUV wavelengths provided by the abundant energy levels of molecular ions. The developed source can have arbitrary polarization states by manipulating the polarization of the pump pulse. It also exhibits a spectral bandwidth of 5∼7 cm −1, a divergence angle of 3∼5 mrad, a pulse duration of ∼10 ps, and a photon flux of ∼10 10 photons/s. The superior temporal and spectral properties give rise to a broadband Raman comb in the DUV/VUV region.